Hypokalemia Correlates with Troponin levels in Moderate-Severe COVID-19 Patients, Independent to Coagulation Status - Friska Anggraini Helena Silitonga; Nur Alaydrus; Andreas Arie Setiawan; Shila Lupiyatama; Charles Limantoro (Medica Hospitalia : Journal of Clinical Medicine, 2025)
Background: Myocardial injury is a common complication of COVID-19, often marked by elevated cardiac troponin and linked to poorer outcomes. Besides recognized causes such as viral injury, inflammation, and coagulopathy, electrolyte disturbances like hypokalemia may also increase cardiac vulnerability. SARS-CoV-2 can promote potassium loss through activation of the renin angiotensin aldosterone system, but the relationship between low potassium and troponin elevation remains unclear. Aim: To evaluate whether serum potassium levels are associated with troponin elevation in patients hospitalized with moderate to severe COVID-19, and whether this association is influenced by disease severity or D-dimer levels. Methods: Cross-sectional study of 50 adults with moderate or severe COVID-19. Serum potassium, troponin, and D-dimer were measured once during admission. Associations were tested using independent t-tests, Mann-Whitney tests, and Fisher’s exact tests, with p < 0.05 considered significant. Results: Among 50 patients (39 moderate, 11 severe COVID-19), 35 (70%) had normal potassium, 12 (24%) hypokalemia, and 3 (6%) severe hypokalemia; 9 (18%) had elevated troponin. Potassium was lower in patients with elevated troponin than in those with normal levels (3.53 ± 0.53 vs. 3.99 ± 0.58 mmol/L, p = 0.038), and potassium status was significantly associated with troponin elevation (p = 0.0401). No significant differences were detected when patients were grouped by disease severity, with potassium (p = 0.44) and troponin (p = 0.66) levels similar in moderate and severe cases. D-dimer levels were not significantly different by severity (p = 0.175) and showed no association with potassium (p = 0.24) or troponin (p = 0.91). Conclusion: In hospitalized patients with moderate to severe COVID-19, lower potassium levels were associated with elevated troponin, regardless of disease severity and without a detectable link to D-dimer status. These findings suggest hypokalemia may contribute to myocardial injury in COVID-19 and support regular monitoring and timely correction of electrolyte disturbances.